2017
DOI: 10.1103/physreve.95.043207
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic laser hosing instability suppression and electron acceleration in a preformed plasma channel

Abstract: The hosing processes of a relativistic laser pulse, electron acceleration, and betatron radiation in a parabolic plasma channel are investigated in the direct laser acceleration regime. It is shown that the laser hosing instability would result in the generation of a randomly directed off-axis electron beam and radiation source with a large divergence angle. While employing a preformed parabolic plasma channel, the restoring force provided by the plasma channel would correct the perturbed laser wave front and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…As confirmed by the simulations, the FSSA mechanism is realized due to the relativistically induced transparency [28][29][30] in a structured target that mitigates instabilities [20,[62][63][64]. This implies that the electron density in the propagation region is n e a 0 n cr , where…”
supporting
confidence: 59%
See 1 more Smart Citation
“…As confirmed by the simulations, the FSSA mechanism is realized due to the relativistically induced transparency [28][29][30] in a structured target that mitigates instabilities [20,[62][63][64]. This implies that the electron density in the propagation region is n e a 0 n cr , where…”
supporting
confidence: 59%
“…The channel inside the target is required for the stable laser pulse propagation. The target structure suppresses the hosing instability that would develop in a uniform target [64]. Additional simulations for a uniform target with n e = 1.5n c confirm that the laser pulse experiences a significant deviation from its original direction after propagating just tens of microns into the target.…”
Section: Supplemental Materialsmentioning
confidence: 72%
“…Additional studies have shown that the laser propagation becomes unstable in a dense relativistically transparent target 54 , which makes the direction of the laser beam propagation unpredictable. One way to suppress the instability while retaining the advantages of laser propagation through a dense plasma is to use structured targets that provide optical guiding to the laser pulse.…”
Section: Main Modelmentioning
confidence: 99%
“…This fraction increases during the interaction, as the channel expands appreciably. An important consideration for choosing R ch /w 0 is the suppression of instabilities that cause the laser beam to deviate from its original direction of propagation 47 . For example, we found that the propagation becomes unstable at R ch /w 0 ≥ 1.…”
Section: Baseline Case -Photon Emission Driven By a 1 Pw Laser Pulsementioning
confidence: 99%
“…Our previously published results indicate that a structured target with a channel serving as an optical wave-guide delivers a well-directed photon beam 11,12 . In contrast to that, laser propagation is unstable in dense relativistically transparent targets 47 , which makes the direction of the emitted photon beam unpredictable. The optical guiding is achieved by filling the channel with a material that becomes very transparent at the peak intensity 48 .…”
Section: Introductionmentioning
confidence: 99%